Purification and characterization of DNA methyltransferases from Neisseria gonorrhoeae. - Piekarowicz, A (1988)
Three DNA methyltransferases, M.NgoAI, and M.NgoBI and M.NgoBII, free of any nuclease activities were isolated from Neisseria gonorrhoeae strains WR220 and MUG116 respectively. M.NgoAI recognizes the sequence 5' GGCC 3' and methylates the first 5' cytosine on both strands. M.NgoBI and M.NgoBII recognize 5' TCACC 3' and 5' GTAN5CTC 3' respectively. M.NgoBII methylates cytosine on only one strand to produce 5' GTAN5mCTC 3'.